"It's Not My Fault!" Status, Attributions, and Perceptions of Injustice: The Case of Custodians and Teachers. Issue 5 (3rd September 2017) - Scheuerman, Heather L.; Hegtvedt, Karen A.; Johnson, Cathryn
ABSTRACT: Perceptions of injustice rely upon a sense-making process in which individuals attempt to understand why and how it occurs. We draw from the attribution-of-blame model of justice judgments to examine how two work groups of disparate status make sense of the treatment and outcomes engendered by their interactions. Data from 27 in-depth interviews with custodians and teachers reveal that when custodians perceive disrespect from teachers and teachers perceive that custodians do not fulfill properly their duties, their attributions are shaped by their status position. Although both make internal attributions to each other for their injustice, teachers do not recognize how they perpetrate injustice against custodians and custodians perceive greater injustice by identifying how external factors affect their performance and blame. This unjustified blame fosters counterproductive work behaviors, illustrating how interdependencies fuel a cycle of injustice. We discuss the implications of these findings for the school and justice processes.